The thought structure of Romans with special references to chapter 6 - Kaye, Bruce Norman (Austen, TX Schola, 1979)
Includes bibliographical references and index.
a dissertation presented to the Faculty of Theology of the University of Basel, for the degree of Doctor of Theology
Keywords: Bible. N.T. Romans -- commentaries